Rauwolfia Serpentina Ameliorates Hyperglycemic, Haematinic and Antioxidant Status in Alloxan- Induced Diabetic Mice - Muhammad Bilal Azmi & and Shamim A. Qureshi (Journal of Applied Pharmaceutical Science, 2013)
To investigate the effect of methanolic root extract (MREt) of Rauwolfia serpentina on hyperglycemic, haematinic and antioxidative dysfunction associated with alloxan-induced diabetes. Mice were divided into normal and alloxan-induced diabetic groups, the second group was sub-divided into three MREt (10, 30 & 60mg/kg) treated test groups and three diabetic (distilled water 1ml/kg), negative (0.05% dimethyl sulphoxide 1ml/kg) and positive (glibenclamide 5mg/kg) control groups. Each treatment was done orally for 14 days. The MREt significantly reduced blood glucose level by improving the body weights, glycosylated hemoglobin (HbA1c) to total hemoglobin (Hb) ratio, red blood cell (RBC) & white blood cell (WBC) counts, packed cell volume (PCV), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration (MCHC) in test groups. Beside this, extract decreases the percent inhibition of catalase (CAT) & superoxide dismutase (SOD) enzymes and restores the liver function by recovering the total protein concentration and normalizing the levels of alanine transaminase (ALT), aspartate transaminase (AST) & alkaline phosphatase (ALP) in test mice. Therefore, MREt ameliorates hyperglycemic, haematinic and antioxidant status in alloxan-induced diabetic mice. Further work is still required to find out the active principle in same extract involved in antidiabetic activity.
Keywords: Antioxidant enzymes, complete blood profile, hypergl